Physiological, hematological and biochemical profile of growing Murrah buffaloes exposed to heat stress in control climatic chamber - SINGH, S V; BHAN, CHANDRA (The Indian Journal of Animal Sciences, 2020)
Six growing buffaloes were exposed under natural ambient conditions (23±0.54°C) and in a climatic chamber at 42±1°C (exposure-I) and 44±1°C (exposure-II) with a relative humidity of 40±2% 4 h for daily for a period of three days continuously. Blood samples from these animals were collected before exposure and at the end of 4 h of exposure and analyzed for hematological parameters (RBC, WBC, Hb and PCV), enzymatic activity, viz. Alkaline phosphatase (ALP), Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Lactate dehydrogenase (LDH) and Acetylcholinesterase (AchE) and cortisol hormone. The physiological responses, viz. RR, PR, RT and ST were also monitored at the similar interval. RR, PR, RT and ST increased significantly due to exposure at both the exposure conditions, but the magnitude of increase in these parameters were significantly higher at second exposure than first exposure. The hematological parameters decreased significantly with the exposure of animals for four hours at both the climatic chamber conditions. The enzymatic activities in blood plasma were significant higher after 4 h of exposure at both the climatic chamber conditions than natural exposure. The pre-exposure levels of cortisol were lower at natural (23±0.54°C) exposure compared to exposure at both the conditions. After exposure at 42°C and 44°C for 4 h, the levels of cortisol increased significantly over pre-exposure values. Exposure to elevated temperatures resulted in significant deviation in physiological, hematological, biochemical and hormone profile of growing buffaloes compared to natural exposure (comfortable temperature) indicating stressful conditions to growing buffaloes. Therefore, growing buffalo needs protection from heat stress conditions for maintaining homeothermy and diverting the available nutrients towards better growth.